Frequent alternate wetting and drying irrigation mitigates the effect of low phosphorus on rice grain yield in a 4‐year field trial by increasing soil phosphorus release and rice root growth. (21st April 2020) - Xu, Feiyun; Song, Tao; Wang, Ke; Xu, Weifeng; Chen, Guanglei; Xu, Min; Zhang, Qian; Liu, Jianping; Zhu, Yiyong; Rensing, Christopher; Zhang, Jianhua; Yuan, Wei
Abstract: The nonrenewable nutrient phosphorus (P) has low mobility in soil and is often present in forms that are unavailable to crop plants. Alternate wetting and drying irrigation is one of the widely promoted water‐saving irrigation techniques and can increase mineral nutrient availability; however, its interaction with P in paddy fields remains unclear. We conducted a 4‐year field experiment to determine whether a specific regime of frequent alternate wetting and drying (FAWD15) irrigation and low P usage (P45) had synergistic effects on rice yield, rice growth, water use efficiency (WUE), agronomic P use efficiency (AEp), and soil residual fertilizer P. We found that compared to the continuously flooded (CF) irrigation, FAWD15 irrigation maintained rice yield under low P usage condition in a 4‐year field trial. Our results also showed that under low P usage, FAWD15 resulted in high AEp and WUE, and reduced residual fertilizer P. Further, FAWD15 irrigation increased labile P release and resulted in increased root growth by improving root sucrose distribution. These results suggest that FAWD15 irrigation can mitigate the effect of low P usage on rice grain yield by increasing soil P release and root growth in paddy fields. Abstract : The nonrenewable nutrient phosphorus (P) has low mobility in soil and is often present in forms that are unavailable to crop plants. Alternate wetting and drying irrigation is one of the widely promoted water‐saving irrigation techniques and can increase mineral nutrient availability; however, its interaction with P in paddy fields remains unclear. We conducted a 4‐year field experiment to determine whether a specific regime of frequent alternate wetting and drying (FAWD15) irrigation and low P usage (P45) had synergistic effects on rice yield, rice growth, water use efficiency (WUE), agronomic P use efficiency (AEp), and soil residual fertilizer P. These results suggest that FAWD15 irrigation can mitigate the effect of low P usage on rice grain yield by increasing soil P release and root growth in paddy fields.